Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50886
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Inlet Boundary Layer Thickness on Rotating Stall in an Axial Compressor

Abstract: A three-dimensional numerical simulation was conducted to study an effect of the inlet boundary layer thickness on the rotating stall in an axial compressor. The inlet boundary layer thickness had significant effects on the hub-corner-separation in the junction of the hub and the suction surface. The hub-corner-separation grew significantly for the thick inlet boundary layer as the load was increased, while it was diminished to be indistinguishable from the rotor wake for the thin inlet boundary layer and a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, this impact of flow instability on a whole system of gas turbine should be avoided. Many studies have been carried out to alleviate the stall and surge phenomena and to improve the operating stability of axial compressor through experiments and numerical analysis by many researchers together with the history of compressors [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this impact of flow instability on a whole system of gas turbine should be avoided. Many studies have been carried out to alleviate the stall and surge phenomena and to improve the operating stability of axial compressor through experiments and numerical analysis by many researchers together with the history of compressors [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The loss characteristic and stall cell size were significantly influenced by the inlet boundary layer thickness according to Choi. 24,25 Wang 26 proposed that the thick inlet boundary layer reduced the working range and enhanced the secondary flow. As for the influence of the inlet boundary layer on CEW optimization, Li 27 found that there was a great difference in the optimal CEW geometry in cases with and without boundary layer skew.…”
Section: Introductionmentioning
confidence: 99%